Ancient DNA from an extinct Mediterranean micromammal—Hypnomys morpheus (Rodentia: Gliridae)—Provides insight into the biogeographic history of insular dormice. (25th November 2019) - Bover, Pere; Mitchell, Kieren J.; Torres‐Roig, Enric; Llamas, Bastien; Thomson, Vicki A.; Alcover, Josep Antoni; Agustí, Jordi; Cooper, Alan; Pons, Joan
Abstract: The dormice (Gliridae) are a family of rodents represented by relatively few extant species, though the family was much more species‐rich during the Early Miocene. Intergeneric phylogenetic relationships among glirids in some cases remain unresolved, despite extensive molecular and morphological analyses. Uncertainty is greatest with respect to the relationships among fossil taxa and how extinct lineages are related to modern species. The fossil genus Hypnomys from the Balearic Islands (western Mediterranean Sea) includes the Late Pleistocene–Holocene species Hypnomys morpheus, which has variously been considered a close relative or subgenus of the extant Eliomys . In the present study, we sequenced ancient mitochondrial DNA from H .  morpheus, which suggests a sister relationship with the extant members of Eliomys . In addition, the pairwise sequence variation between Hypnomys and Eliomys is higher than that observed between congeneric glirid species (e.g., many Graphiurus spp.), which allows us to reject the hypothesis that Hypnomys is a subgenus of Eliomys . Our molecular dating analyses suggest that Hypnomys and Eliomys diverged 13.67 million years ago (95% highest posterior density [HPD] = 7.39–20.07). The relatively early split between these genera together with the molar morphology of early representatives of Hypnomys points to a Middle‐Late Miocene origin from a continental glirid with a complex molar pattern, such as Vasseuromys or a closely related genus. Abstract : We infer a sister relationship of the extinct Balearic dormouse Hypnomys morpheus with the extant members of Eliomys using fragments of mitochondrial genes. Sequence variation between Hypnomys and Eliomys allows us to reject the hypothesis that Hypnomys is a subgenus of Eliomys . Our analyses suggest that Hypnomys and Eliomys diverged 13.67 million years ago, which together with the molar morphology of early representatives of Hypnomys points to a Middle‐Late Miocene origin from a continental glirid with a complex molar pattern.